1972
DOI: 10.2307/3896904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wildfire on Timber and Forage Production in Arizona

Abstract: A severe May wildfire decimated an unthinned ponderosa pine stand in northern Arizona, while an adjacent thinned stand was relatively undamaged. Radial growth increased on burned trees where crown kill was less than 60% and decreased where crown kill was more than 60%. Burning initially stimulated growth of herbaceous vegetation in both stands. Herbage nutrient value was temporarily enhanced due to burning. Artificially seeded areas produced most herbage 2 years after burning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

1976
1976
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 6 publications
2
31
0
6
Order By: Relevance
“…Residual ash found on the soil surface is typically enriched with P and cations that are normally retained onsite and available for subsequent assimilation by emerging vegetation (Woodmansee and Wallach, 1981b;Wright and Bailey, 1982;Debano and Klopatek, 1988;Riggs et al, 1996). Not only do these enhanced chemical conditions encourage plant growth, but the improved nutritional status of emerging herbaceous plants increases the forage value of vegetation consumed by herbivores (Pearson et al, 1972;Hobbs and Spowart, 1984;DeByle et al, 1989;Carreira and Niell, 1992). The only difference between ®re treatments was the generally higher levels of foliar Mg on plots burned during the dormant season than on those burned in the growing season.…”
Section: Plant Nutrients and Soil Chemistrymentioning
confidence: 99%
“…Residual ash found on the soil surface is typically enriched with P and cations that are normally retained onsite and available for subsequent assimilation by emerging vegetation (Woodmansee and Wallach, 1981b;Wright and Bailey, 1982;Debano and Klopatek, 1988;Riggs et al, 1996). Not only do these enhanced chemical conditions encourage plant growth, but the improved nutritional status of emerging herbaceous plants increases the forage value of vegetation consumed by herbivores (Pearson et al, 1972;Hobbs and Spowart, 1984;DeByle et al, 1989;Carreira and Niell, 1992). The only difference between ®re treatments was the generally higher levels of foliar Mg on plots burned during the dormant season than on those burned in the growing season.…”
Section: Plant Nutrients and Soil Chemistrymentioning
confidence: 99%
“…Although investigations in Arizona by Pearson et al (1972), Campbell et al (1977, and in central Washington (Weaver 1951) have been made, Mueggler (1976) concluded that generalizations are difficult because each combination of climate, vegetation, and soil must be considered separately. Further, none of these investigations evaluated trends in productivity, vegetative composition, and nutrient content simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that herbaceous plants growing on burned area contain more crude protein [22 -25] , less crude fiber [22,23,26] . Thus, the food digestible rate is increased [27] Sciences (KZCX3-SW-343) and "Xi Bu Zhi Guang" Project of CAS and (200233104) and Mr. Wolfgang Frey (former editor of German Journal of Wildlife ) for financing this research.…”
Section: Food Habitat Use Of Tarim Red Deermentioning
confidence: 99%